Ideas, institutions, processes: essays in memory of Satish Saberwal - Jayaram N (ed.) (Hyderabad: Orient Blackswan, 2014)
Satish Saberwal, Indian sociologist; contributed articles; some previously published.
Keywords: Social Institutions India; Sociology India; Social Sciences